HUBUNGAN JENIS PROSTHETIC FOOT TERHADAP HIPEREKSTENSI DAN KELEMAHAN LIGAMEN PADA PENGGUNA PROSTHESIS TRANSTIBIAL: Indonesian - Dwi Setyawan; Muhibbah Fatat (Medical Journal of Nusantara, 2024)
Background: Amputation can be defined as the act of separating part of the body, part or all of an extremity. Currently, lower limb amputations account for 85-90% of all amputations and transtibial amputation is the most frequently performed type of amputation surgery. One of the problems with transtibial amputation is hyperextension and weakness of the ligaments in the knee. Knee hyperextension is a condition that occurs when the knee joint is extended (straightening the knee) excessively, thus putting pressure on the structure of the knee and the back of the knee joint. Ligament weakness in the knee is weakness in the anterior cruciate ligament, posterior cruciate ligament, medial collateral ligament and lateral collateral ligament. Choosing the right prosthesis components can overcome this. One component that plays an important role is the foot component. Methods: This type of research is observational analytic with a cross-sectional design. The research subjects were 17 transtibial prosthesis users. Data analysis in this study used Spearman Rank Test. Results: Based on the Spearman Rank results, the significance result was 0.653 for the type of foot with hyperextension, while for the type of foot with ligament weakness, the significance result was 0.434. Both variables had variable values > 0.05, meaning there was no correlation between foot type and hyperextension and ligament weakness in transtibial prosthesis users. Conclusion: There is no correlation type of foot to hyperextension and ligament weakness. In future research, it is hoped that research can be carried out with a larger number of samples and a more varied type of foot.